Career Preparation of Primary School Pupils in Tanzania - Amani, Jaquiline Amani (Papers in Education and Development, 2023)
This study employed a survey design under quantitative research approach, to explore subject preferences, career aspirations, and sources of career information of 287 primary school pupils. A questionnaire with open-ended and closed questions was employed to collect data. The study found that out of ten taught subjects, pupils ranked Kiswahili as their most preferred subject and English as the least preferred subject. In terms of career paths, a total of nine careers were listed for pupils to select the most preferred one. It was revealed that most of the pupils aspired to become medical doctors, teachers, soldiers, and engineers. These pupils ' career aspirations emerged to be gender-stereotyped, with only a few girls showing a keen interest in science and engineering fields. Moreover, the pupils identified their parents as the most trusted sources of information on careers. Based on these findings, career preferences appear to unfold during childhood with a range of factors such as parents, teachers and the quality of career information received through socialisation nurturing and shaping these choices. Keywords: career aspirations, primary pupils subject preferences, sources of career information.